2017
DOI: 10.1002/etep.2351
|View full text |Cite
|
Sign up to set email alerts
|

Implementation aspects and comprehensive assessment of a 16 MVAr static VAr compensator installed for a weak distribution network

Abstract: Summary Voltage regulation at weak distribution networks and feeders imposes several challenges. The degree of complexities of the overall design and implementation is network and site dependent. In this paper, design and implementation of a thyristor controlled reactor–based static VAr compensator (SVC) system to enhance voltage regulation and avoid voltage instability are presented and discussed. The SVC system is installed for an extremely weak distribution network with long feeders in a remote area in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The result showed that this method was fast, effective, and reliable. Alabduljabbar et al 6 discussed a design and implementation of thyristor-controlled reactor based on static VAR compensator (SVC) system, in order to improve the voltage regulation ability and avoid voltage instability. They used Power Systems Computer-Aided Design (PSCAD)/Electromagnetic Transients including DC (EMTDC) software to simulate electric power system on remote areas of the kingdom of Saudi Arabia, and the results showed that in the similar case of installing network in extremely weak local distribution, the method was effective.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that this method was fast, effective, and reliable. Alabduljabbar et al 6 discussed a design and implementation of thyristor-controlled reactor based on static VAR compensator (SVC) system, in order to improve the voltage regulation ability and avoid voltage instability. They used Power Systems Computer-Aided Design (PSCAD)/Electromagnetic Transients including DC (EMTDC) software to simulate electric power system on remote areas of the kingdom of Saudi Arabia, and the results showed that in the similar case of installing network in extremely weak local distribution, the method was effective.…”
Section: Introductionmentioning
confidence: 99%
“…Design of D‐STATCOM of ±250 kVAr for 1.6‐MVA distribution substation in Tehran to was established in Tavakoli Bina et al to control voltage regulation and to reduce unbalances. Voltage regulation of real time that existed in Saudi Arabia distribution network using 16‐MVAr STATCOM is addressed in Alabduljabbar et al Dynamic reactive power compensation provided with D‐STATCOM in 44‐kV weak industrial distribution systems to maintain acceptable voltage profiles and prevent process shutdowns. Various optimization and sensitivity based techniques were used by many authors to determine optimal location and rating of D‐STATCOM in radial distribution systems to minimize power losses.…”
Section: Introductionmentioning
confidence: 99%